Laboratory study of astrophysical collisionless shock at SG-II laser facility. (4th September 2018) - Yuan, Dawei; Wei, Huigang; Liang, Guiyun; Wang, Feilu; Li, Yutong; Zhang, Zhe; Zhu, Baojun; Zhao, Jiarui; Jiang, Weiman; Han, Bo; Yuan, Xiaoxia; Zhong, Jiayong; et al.
Abstract : Astrophysical collisionless shocks are amazing phenomena in space and astrophysical plasmas, where supersonic flows generate electromagnetic fields through instabilities and particles can be accelerated to high energy cosmic rays. Until now, understanding these micro-processes is still a challenge despite rich astrophysical observation data have been obtained. Laboratory astrophysics, a new route to study the astrophysics, allows us to investigate them at similar extreme physical conditions in laboratory. Here we will review the recent progress of the collisionless shock experiments performed at SG-II laser facility in China. The evolution of the electrostatic shocks and Weibel-type/filamentation instabilities are observed. Inspired by the configurations of the counter-streaming plasma flows, we also carry out a novel plasma collider to generate energetic neutrons relevant to the astrophysical nuclear reactions.